Room-temperature continuous-wave vertical-cavity surface-emitting lasers based on 2D layered organic–inorganic hybrid perovskites - Zhang, Hongbo (2021)
Two-dimensional (2D) layered lead halide perovskites with large exciton binding energies, efficient radiative recombination, and outstanding environmental stability are regarded as supreme candidates for realizing highly compact and ultralow threshold lasers. However, continuous-wave (CW) pumped lasing of 2D lead halide perovskites, as the precondition for the electrically pumped lasing, is still challenging. Here, we tackled this challenge by demonstrating lasing emission in phenylethylammonium lead iodide [(PEA)2PbI4] embedded in a vertical microcavity under continuous pumping at room temperature. The millimeter-sized (PEA)2PbI4 single crystal was obtained from a two-step seed-growth method, showing high crystallization, excellent thermal stability, and outstanding optical properties. We used the exfoliated (PEA)2PbI4 thin flake as the gain medium to construct a vertical-cavity surface-emitting laser (VCSEL), showing robust single-mode CW lasing operation with an ultra-low threshold of 5.7 W cm−2 at room temperature, attributed to strong optical confinement in the high-Q cavity. Our findings provide a strategy to design and fabricate solution-based 2D perovskite VCSELs and mark a significant step toward the next-generation of coherent light sources.